Pengaruh Penyinaran UV-C Terhadap Perubahan Mutu Fisik Cabai Merah (Capsicum annuum L.) Selama Penyimpanan - Indriyani, Maulidya; Novita, Dwi Dian; Kuncoro, Sapto (Jurnal Agricultural Biosystem Engineering, 2023)
Marketing of red chili outside Lampung Province requires farmers to carry out proper postharvest handling to maintain high quality chili until it reaches consumers. One of them is by using ultraviolet (UV-C) sterilization. This study aims to study the effect of distance and duration of UV-C irradiation on 9 treatment combinations on 4 parameters of the physical quality of chilies, namely weight loss, hardness level, moisture content, and freshness during storage, and determine the best treatment. The experimental design used was 2-factor RAL. The first factor is the irradiation distance which consists of 3 levels, namely 20 cm (d1), 40 cm (d2), and 60 cm (d3). The second factor is the duration of irradiation which consists of 3 levels, namely 10 minutes (t1), 20 minutes, (t2) and 30 minutes (t3). Data were analyzed using ANOVA at level α = 5% and Duncan’s Advanced Test. The conclusions obtained were: (1) treatment distance and duration of irradiation had a significant effect on 2 parameters of physical quality of chili, namely water content and level of freshness but had no effect on 2 other parameters, namely weight loss and degree of hardness during 8 days of storage, (2) treatment of irradiation distance 60 cm and 20 minutes of irradiation time (d3t2) was the best treatment in this study. Keywords: chili, UV-C, irradiation distance, irradiation time, storage